Workshop untuk Pembuatan Bahan Ajar Ilmu Pengetahuan Alam Berbasis Kearifan Lokal Sidoarjo - Noly Shofiyah; Fitria Nur Hasanah; Siti Miluningtias (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
The main problem that occurred in SMP Negeri 2 Jabon, which inspired this activity was the pedagogical competence of science teachers on aspects of making teaching materials and the implementation of science learning in the classroom that had not yet integrated local wisdom into science learning. In other words when making teaching materials teachers rarely associate the concept of science with local culture in Sidoarjo. Therefore, in order for teachers to be able to make teaching materials based on local wisdom or ethnoscience, a workshop was held with the aim of: 1) Improving teacherÃ¢â‚¬â„¢s concepts understanding of ethnoscience, local wisdom or local culture, 2) Enhancing teacher skills in making teaching materials based on local wisdom. In delivering innovations to partners, it is carried out by the method of explanation, discussion, practice and mentoring and evaluation stages. The result of this activity is the knowledge of teachers about learning science based on local wisdom or ethnoscience increased. This is indicated by an average pre-test 58.3 and post-test 76.7. In addition, the teachers are able to make science teaching materials based on local wisdom or ethnoscience. Some of the teaching materials that have been made by the teachers are learning materials integrated with traditional games; Science worksheets with the theme of smoking fish; and worksheets for making Ã¢â‚¬Å“klompenÃ¢â‚¬Â.